Cultural Threads of Faith: Analyzing Yasinan Practices in Mary Pat Fisher's Living Religion - Maulana, Muhammad Rijal (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This paper examines the concept of Living Religion through the Yasinan tradition, a religious activity that plays a significant role in the lives of Muslim communities, particularly in Indonesia. Using the theoretical framework presented in Mary Pat Fisher’s book, Living Religion, this study explores how Yasinan functions as a dynamic expression of Islamic culture, reflecting the interaction between religious teachings, social practices, and local cultural adaptations. The Yasinan ritual, which involves the recitation of Surah Yasin as an act of worship, has become an integral part of many Muslim communities' lives, fostering spiritual solidarity and cultural continuity. The research employs a qualitative method with a descriptive analysis and utilizes library research to gather relevant sources from various forms of literature and digital resources. Through an analysis of the ritual's role in strengthening social bonds and preserving Islamic teachings, the study demonstrates how religious practices like Yasinan evolve within cultural contexts and remain relevant and meaningful in contemporary society. This paper contributes to a deeper understanding of how living religious practices play a vital role in social structures and offers insights into the relationship between religion and culture within modern Islamic communities.